Physiological and pathophysiological mechanisms of the molecular and cellular biology of angiogenesis and inflammation in moyamoya angiopathy and related vascular diseases - Dorschel, Kirsten B.; Wanebo, John E. (Frontiers in Neurology, 2023)
Rationale The etiology and pathophysiological mechanisms of moyamoya angiopathy (MMA) remain largely unknown. MMA is a progressive, occlusive cerebrovascular disorder characterized by recurrent ischemic and hemorrhagic strokes; with compensatory formation of an abnormal network of perforating blood vessels that creates a collateral circulation; and by aberrant angiogenesis at the base of the brain. Imbalance of angiogenic and vasculogenic mechanisms has been proposed as a potential cause of MMA. Moyamoya vessels suggest that aberrant angiogenic, arteriogenic, and vasculogenic processes may be involved in the pathophysiology of MMA. Circulating endothelial progenitor cells have been hypothesized to contribute to vascular remodeling in MMA. MMA is associated with increased expression of angiogenic factors and proinflammatory molecules. Systemic inflammation may be related to MMA pathogenesis. Objective This literature review describes the molecular mechanisms associated with cerebrovascular dysfunction, aberrant angiogenesis, and inflammation in MMA and related cerebrovascular diseases along with treatment strategies and future research perspectives. Methods and results References were identified through a systematic computerized search of the medical literature from January 1, 1983, through July 29, 2022, using the PubMed, EMBASE, BIOSIS Previews, CNKI, ISI web of science, and Medline databases and various combinations of the keywords “moyamoya,” “angiogenesis,” “anastomotic network,” “molecular mechanism,” “physiology,” “pathophysiology,” “pathogenesis,” “biomarker,” “genetics,” “signaling pathway,” “blood-brain barrier,” “endothelial progenitor cells,” “endothelial function,” “inflammation,” “intracranial hemorrhage,” and “stroke.” Relevant articles and supplemental basic science articles almost exclusively published in English were included. Review of the reference lists of relevant publications for additional sources resulted in 350 publications which met the study inclusion criteria. Detection of growth factors, chemokines, and cytokines in MMA patients suggests the hypothesis of aberrant angiogenesis being involved in MMA pathogenesis. It remains to be ascertained whether these findings are consequences of MMA or are etiological factors of MMA. Conclusions MMA is a heterogeneous disorder, comprising various genotypes and phenotypes, with a complex pathophysiology. Additional research may advance our understanding of the pathophysiology involved in aberrant angiogenesis, arterial stenosis, and the formation of moyamoya collaterals and anastomotic networks. Future research will benefit from researching molecular pathophysiologic mechanisms and the correlation of clinical and basic research results.